A process-based framework to examine China's approach to transboundary water management. Issue 5 (3rd September 2018) - Zhang, Hongzhou; Li, Mingjiang
ABSTRACT: As China emerges as a regional and global power and its interest in utilizing the transboundary water resources within its borders continues to grow, a better understanding of China's policies and practices towards transboundary waters is of critical importance. Scholars have explored various approaches to the study of this subject, including the legal perspective, the socioeconomic-environmental lens, the foreign relations/neighbourhood diplomacy angle, and international relations theories. Each approach has its merits and weaknesses. On the basis of all the existing analytical studies, this article proposes a process-based framework to study China's policies towards transboundary water management.